THE DIFFICULTIES OF INDONESIAN STUDENTS IN LEARNING ENGLISH PLURAL FORM: CONTRASTIVE ANALYSIS - Trisnadewi, Komang (Yavana Bhasha : Journal of English Language Education, 2019)
A comparative analysis is needed between the two languages or known as contrastive analysis to identify their structural similarities and differences so that the material and methods of teaching will be appropriate. Further than that, this paper is aimed to give a clear understanding about how Indonesian differs from English in the sense of its language features, especially in plural form. It is known that the structure of the plural between English and Indonesian is different although some similarities were found. Indonesian learners will find it difficult to learn plural words because in terms of word formation, English and Indonesian are very different. The formation of plural words in English is through the process of affixation, while in Indonesian, the formation of plural is through reduplication and addition of quantifier and number. It is necessary to give more explanations and exercises to learn the plural of English because with a lot of practice, it is hoped that Indonesian learners will start to get used to the formation of the plurals.